Effect of uncertainty on the reaction response in fencing - Gutiérrez-Dávila, M.; Rojas, F. J.; Antonio, R.; Navarro, E. (Research Quarterly for Exercise and Sport, 2013)
Purpose: The objective was to determine the way in which the level of uncertainty produced during the execution of a lunge attack with target change (two or four possible responses) affects reaction-response time parameters and kinematic factors involved in the technical coordination of the attack. Method: Seventeen fencers from the Spanish National Men's Fencing Team participated in the study, which involved performing a lunge attack against a moving circle as fast as possible, while attempting to place the tip of the sword inside the circle that appeared in the plastron's center of symmetry. Two force platforms were used to record the anteroposterior component of force and the initiation of movement. Kinematics were measured with a three-dimensional motion-capture system that recorded the spatial positions of 11 markers. An electronic signal was used to time-synchronize all of the systems. Results:The results demonstrate a significant increase in reaction time, p < .01, and choice reaction time, p < .001, when uncertainty increases, while movement time, precision, and segmental participation sequence during movement are not affected when uncertainty increases. Conclusion: It is worth stressing the importance of uncertainty-reduction strategies for fencers' performance to reduce the reaction-response time. Although increased uncertainty has little influence over precision and segmental participation sequence of the movement pattern used in attacks executed by elite fencers, caution should be used when generalizing these results for fencers of a lower technical level than that of the participants in this study.